2008
DOI: 10.1074/jbc.m708456200
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/Annexin V Interactions Regulate Chondrocyte Mineralization

Abstract: Physiological mineralization in growth plate cartilage is highly regulated and restricted to terminally differentiated chondrocytes. Because mineralization occurs in the extracellular matrix, we asked whether major extracellular matrix components (collagens) of growth plate cartilage are directly involved in regulating the mineralization process. Our findings show that types II and X collagen interacted with cell surface-expressed annexin V. ] i , alkaline phosphatase activity, and mineralization. In conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
(71 reference statements)
2
19
0
2
Order By: Relevance
“…More recently, it has been shown that type II and type X collagen bind annexin V, which mediates calcium influx into matrix vesicles. Further, disruption of this interaction resulted in diminished AP activity and mineralization [28]. However, unlike growth plate chondrocytes, type X collagen (and AP) persists in fibrocartilage throughout adulthood, a finding we have confirmed [16, 29, 30].…”
Section: Discussionsupporting
confidence: 72%
“…More recently, it has been shown that type II and type X collagen bind annexin V, which mediates calcium influx into matrix vesicles. Further, disruption of this interaction resulted in diminished AP activity and mineralization [28]. However, unlike growth plate chondrocytes, type X collagen (and AP) persists in fibrocartilage throughout adulthood, a finding we have confirmed [16, 29, 30].…”
Section: Discussionsupporting
confidence: 72%
“…Annexins also play an important role in MV function (2628). Annexins are Ca 2+ and phospholipid binding proteins, which under the right conditions can form calcium channels through MV membranes (26).…”
Section: Enzymes Channels and Transportersmentioning
confidence: 99%
“…MVs contain annexins II, V and VI, and in such membranes, MV annexins appear to be associated with Ca 2+ transport. Moreover, annexin V binds to type II and X collagen and these interactions stimulate its Ca 2+ channel activities leading to increased influx of Ca 2+ into liposomes and matrix vesicles (20,28). …”
Section: Enzymes Channels and Transportersmentioning
confidence: 99%
“…4). Interestingly, it has also been postulated that PS-annexincollagen interactions regulate calcium influx into matrix vesicles and cells in vitro, (74)(75)(76) thereby regulating the concentration of Ca 2þ ions. Mice double-deficient for annexins A5 and A6 did not show any mineralization defects and displayed a normal distribution of matrix vesicles in vivo, showing that bone mineralization is facilitated rather independently of these annexins.…”
Section: Ano6mentioning
confidence: 99%